Selective emitter with core–shell nanosphere structure for thermophotovoltaic systems. (15th January 2022) - Meng, Caifeng; Liu, Yunpeng; Xu, Zhiheng; Wang, Hongyu; Tang, Xiaobin
Abstract: For thermophotovoltaic (TPV) systems, traditional thermal emitters waste considerable energy due to the mismatch between the thermal radiation power spectrum and the bandgap of the photovoltaic (PV) cells. Here, a core–shell nanosphere (CSN) structured selective emitter was designed and optimized on the basis of numerical calculation. By iteratively optimizing the geometric parameters of the CSN emitter, the average emissivity of the CSN emitter exceeds 0.93 within the bandgap and is suppressed to 0.13 outside the bandgap. The mechanism of selective emission characteristics is elucidated in detail. Additionally, the simulation results demonstrate that the CSN emitter exhibits emissivity insensitivity to polarization and incident angle. For the TPV system with the InGaAs cells, an output power density of 0.594 W/cm 2 and a system efficiency of 12.83% are achieved at a CSN emitter temperature of 1338 K. The obtained output power density is relatively high, i.e ., 3.2 times that of the previously reported record (0.184 W/cm 2 ). And ultimately, the core–shell structural nanoparticles were synthesized by solution–processed and their performance was tested. This research improves the performance of the selective emitter and paves the way for a more efficient design of TPV systems. Graphical abstract: Image 1 Highlights: A core–shell nanosphere selective emitter was designed. Geometric parameters of the emitter were optimized on the basis of the FDTD method. Polarization and angle of the emitter are insensit ive. Average emissivity exceeds 0.93 within the bandgap of InGaAs cells. Core–shell nanoparticles were synthesized by solution–processed.